Spaces of exception: southern multilingualisms as resource and risk. Issue 1 (1st January 2019) - Heugh, Kathleen; Stroud, Christopher; Scarino, Angela
ABSTRACT: In this paper we draw attention to people who journey from one temporal and spatial setting towards another in the 'South', who aspire to a reconfigured sense of belonging, prosperity and wellbeing, and their multilinguality and multilingualisms. Through three vignettes of journeys we illustrate how in changing of place that linguistic diversities are encountered and mediated. During moments of North–South and South–South entanglement and exception we argue that multilingualisms re-ecologise along horizontal axes of conviviality, and / or re-index along vertical axes of exclusion. We suggest that 'rooting' and 'rerouting' multilingualisms are not only multidimensional, but they are also multifaceted as people who choose or are obliged to experience dis-placement, undertake journeys of anticipation of replacement into regulated or unregulated situations. Multilingualisms in the memories, dreams, complex selves, materiality and complicities of coping have yet to receive sufficient attention from linguists. We attempt to capture these aspects and suggest that southern multilingualisms have much to offer and entice northern multilingualisms. We illustrate how closely integrated are multilingual repertoires with mobilities and temporalities of dislocation and change; with loss, nostalgia and the anticipation of new beginnings; and with multi-scaled complicities between individuals as they re-calibrate lives in turbulent and changing circumstances.